Zeolite Beta Membranes for the Octane Upgrading of C5/C6 Light Naphta - Silva, José A.C. (2011)
The zeolite Beta membranes were prepared by secondary growth method in asymmetric tubular Al2O3 supports (Inocermic GmbH, Germany), combining three different types of seeding techniques and crystallization conditions. Figure 1 show SEM micrographs of a typical non-calcined beta membrane synthesized in this work (cross section view). The vapour permeation experiments performed in the apparatus shown in Figure 2 with mixtures of nHEX, 3MP, 23DMB and 22DMB show that permeate flux increase as the degree of branching decreases following the order: nHEX>>3MP>23DMB>22DMB. Approximately one third of the feed stream cross the membranes. Figure 3 shows that in the retentate stream the fractions of monobranched and normal hexane isomers (low RON compounds) decrease while the concentration of dibranched isomers (high RON compounds) is increased in relation to the equimolar feed composition. Consequently, the RON can be boosted in retentate up to 3.8 points. These results demonstrate the potential of the zeolite beta membranes for application in the production of additive-free premium gasoline.